QOMARIAH MONTHS EARLIER DEFINITION IN INDONESIA UNDER THE SUPERVISION OF DATA HILAL BMKG - Rukmana Nugraha (Pusbindiklat - LIPI, 2011)
Hilal observations was conducted from October 2008 to April 2010 using a telescope and electronic detec-tor. The data obtained were analyzed based on the measurement and the calculation of delta azimuth, arc of vision, arc of light, age and lag time stated at best time for observed Hilal or at sunset/sunrise for unobserved Hilal. For delta azimuth 0o, Hilal can be observed if arc of vision was greater than 8,95o, arc of light was greater than 8,33o, age more than 12,08 hour after/before conjunction and lag was longer than 28,97 minutes. Based on these criteria, Ramadhan, Shawal, and Dhulhijjah 1431 H will begin on 12 August 2010, 10September 2010, and 8November 2010, respectively.